Mathematical design of fretting wear of interface of shaft with rolling bearing - Фастовець, П.М. (Problems of Tribology, 2014)
It is developed mathematical model of fretting wear processes of interface of the shaft with a frictionless bearing, which considers the sizes and kinematics parameters of interface, radial loading and physic-mechanical properties of conjugated surfaces. The model enables to forecast dynamics of wear process of interfaces of type “the shaft - frictionless bearing” in nodes of machines and their resource.